2014
DOI: 10.1177/1932296814528434
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Monitors

Abstract: How patients are benefitting from continuous glucose monitoring (CGM) remains poorly understood. The focus on numerical glucose values persists, even though access to the glucose waveform and rate of change may contribute more to improved control. This pilot study compared outcomes of patients using CGMs with or without access to the numerical values on their CGM. Ten persons with type 1 diabetes, naïve to CGM use, enrolled in a 12-week study. Subjects were randomly assigned to either unmodified CGM receivers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…We found associated improvement in engagement with care, reduction in HbA1c, sustained CGM use, and decrease in DKA admissions. In this case series, we observed reduction in fear of hypoglycemia, which is a previously described benefit of CGM technology [ 22 ]. The remote monitoring program provided frequent short touch-points for CDCES to help families troubleshoot diabetes management issues and learn to navigate the health system, such as calling suppliers monthly to reorder supplies, reaching out to suppliers for replacements, and contacting the diabetes team for medical issues.…”
Section: Discussionsupporting
confidence: 62%
“…We found associated improvement in engagement with care, reduction in HbA1c, sustained CGM use, and decrease in DKA admissions. In this case series, we observed reduction in fear of hypoglycemia, which is a previously described benefit of CGM technology [ 22 ]. The remote monitoring program provided frequent short touch-points for CDCES to help families troubleshoot diabetes management issues and learn to navigate the health system, such as calling suppliers monthly to reorder supplies, reaching out to suppliers for replacements, and contacting the diabetes team for medical issues.…”
Section: Discussionsupporting
confidence: 62%
“…The number of people participating in this study was determined using the first-type error with 0.05 and the second-type error 0.8; and using the amount of fear of hypoglycemia in the study of Walker et al [ 28 ], 36 patients in each group. The inclusion criteria were: having diabetes type 2, hypoglycemic experience and diagnosed with the fear of hypoglycemia, no history of mental disorders, no visual impairment and strabismus, older than 25 years, no history of seizure, and full consent to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Since then, engineers have been improving the system to monitor blood glucose levels in real time without constant pricking; it also shows trends in the change of current blood glucose levels and is able to sound an alarm in case of hyperglycaemia or hypoglycaemia, which greatly affects both quality of life as well as glycaemic control -Miller et al [10] presented data from a study in which they compared their group with a cohort obtained from a national registry, supporting the thesis that frequent blood glucose monitoring helps in lowering HbA 1c , due to the patient being more engaged in the treatment. An interesting study was performed by Walker [11] in which the authors aimed to establish whether knowing the blood glucose level which is shown in the CGM might have effect on the therapy. Therefore, their experimental group received a modified CGM where glucose numbers were obscured, while the control group received an unmodified CGM.…”
Section: Constant Glucose Monitoringmentioning
confidence: 99%